Effect of Dietary Supplementation with Probiotic or Essential Oils on Growth Performance of Broiler Chickens - Chalghoumi , R.; Belgacem, A.; Trabelsi, I.; Bouatour, Y.; Bergaoui, R. (International Journal of Poultry Science, 2013)
This experiment was conducted to investigate the effect of the dietary supplementation of a probiotic (Lactobacillus plantarum strain TN8) or a commercial blend of essential oils (clove and cinnamon essential oils) on growth performance of broiler chicken. The dietary treatments were: basal diet as control (C); basal diet plus probiotic (0,2% of Lactobacillus plantarum strain TN8 at 2x1010 cfu/g; P); basal diet plus essential oils blend (300 mg/kg; EOB). A total of 900 one-day old male broiler chicks were randomly allocated to 3 experimental groups of 6 replicates of 50 chicks each. The chicks were grown to 35 d of age. Body weight, feed intake and feed conversion were weekly determined. The mortality was recorded daily. Concerning weight gain, in the periods of 8-14, 15-21 and 22-28 days of age, the group fed the essential oils blend presented significantly (p